Locally produced CD19 CAR T cells leading to clinical remissions in medullary and extramedullary relapsed acute lymphoblastic leukemia. Issue 12 (26th September 2018) - Jacoby, Elad; Bielorai, Bella; Avigdor, Abraham; Itzhaki, Orit; Hutt, Daphna; Nussboim, Vered; Meir, Amilia; Kubi, Adva; Levy, Michal; Zikich, Dragoslav; Zeltzer, Li‐at; Brezinger, Karin; et al.
Abstract: Autologous CD19 chimeric‐antigen receptor (CAR) T cells demonstrated remarkable remission rates in relapsed and refractory acute lymphoblastic leukemia (R/R ALL). Here, we report results from a phase 1b/2 study of in‐house produced CD19 CAR with a CD28 costimulatory domain. Twenty‐one patients with R/R ALL were enrolled, and 20 infused. The median age was 11 years (range, 5‐48). Patients had a median of 4 prior regimens, including blinatumomab in 6 and prior stem–cell transplantation in 10. In total 8 patients had extramedullary (EM) leukemic involvement, and prior to lymphodepletion and CAR 7 had active lesions, a group underrepresented in previous trials. In vivo expansion of CAR T cells was observed in 18 patients. In total 16 patients developed cytokine release syndrome, and 11 patients developed neurotoxicity, with no toxic deaths. All responding patients were referred to an allogeneic hematopoietic stem‐cell transplantation. The remission rate was 90%, including resolution of all refractory EM sites. Four responding patients relapsed, 3 who had a PCR‐MRD positive remission at 28 days following CAR‐T cells and 1 patient 21 months after an MRD‐negative response. The estimated 1‐year event‐free survival and overall survival are 73% and 90%, respectively. Patients with R/R EM ALL may also benefit from CAR‐T cell therapy.